2008
DOI: 10.1007/s10519-008-9211-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects Exceed Genetic Effects on Perceived Intensity and Pleasantness of Several Odors: A Three-Population Twin Study

Abstract: Human genes encoding odorant receptors have been identified, but the contribution of genetic effects to total variation in specific odor perceptions is largely unknown. We estimated the relative contributions of genetic and environmental effects to variation in the perceived intensity and pleasantness of cinnamon, chocolate, turpentine, and isovaleric acid (sweaty) odors by quantitative genetic modeling of odor rating data from 856 twin individuals (including 83 complete monozygotic and 275 dizygotic twin pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 37 publications
1
19
1
Order By: Relevance
“…Interestingly, the genetic variations of the GNAT3 gene also explained 13% of the variation in sweet taste perception [83]. Another study of female monozygotic and dizygotic twins reported that genetics accounts partly for the ability to perceive the intensity of a sweet (sucrose) solution and for the liking of sweet foods [84], suggesting that liking of sweet-tasting foods is a multifactorial, polygenic trait [85]. …”
Section: Possible Functions Of Sweet Taste Perceptionmentioning
confidence: 99%
“…Interestingly, the genetic variations of the GNAT3 gene also explained 13% of the variation in sweet taste perception [83]. Another study of female monozygotic and dizygotic twins reported that genetics accounts partly for the ability to perceive the intensity of a sweet (sucrose) solution and for the liking of sweet foods [84], suggesting that liking of sweet-tasting foods is a multifactorial, polygenic trait [85]. …”
Section: Possible Functions Of Sweet Taste Perceptionmentioning
confidence: 99%
“…For instance, the ability to smell food odors like chocolate or lemon is associated with little or no heritability. 148,149 However, the pleasantness of cinnamon is heritable and has been mapped to chromosome 4 by linkage analysis. 150 If the allelic genes that determine the pleasantness of odors like cinnamon are identified, studies of genotype and food intake might be worthwhile.…”
Section: Smellmentioning
confidence: 99%
“…In order to investigate hedonic impressions elicited by olfactory stimuli, functional MRI has been used with increasing frequency during the last decade (Fulbright et al, 1998; Royet et al, 2000; Zatorre et al, 2000; Bensafi et al, 2002b; Jacob et al, 2003; Rolls et al, 2003; Konstantinidis et al, 2006; Grabenhorst et al, 2007; Knaapila et al, 2007, 2008; Lapid et al, 2008; Katata et al, 2009; Kermen et al, 2011). Olfactory-visual cross-modal phenomena may be approached by studying the effect of olfaction on visual cues, or vice versa, the effect of vision on olfactory processing, or by simultaneous presentation of both odors and images.…”
Section: Introductionmentioning
confidence: 99%